Variabel Penentu Loyalitas Melalui Kepuasan Pada Katering Sehat - Meytianni, Devia Fajar; Meliana, Vina (Research and Community Service UNIVERSITAS KALBIS, 2024)
This study aims to determine the influence of service quality, price and brand trust on customer loyalty through Customer satisfaction. This study uses a quantitative method with purposive sampling techniques sampling. The respondents of this study were 215 who had consumed Yellow Fit Kitchen's healthy catering. The data analysis techniques used are simple regression and path analysis tests. The results of this study show that service quality affects Customer satisfaction, price affects Customer satisfaction, brand trust affects Customer satisfaction and Customer satisfaction affects customer loyalty.